2020
DOI: 10.3390/antiox9010062
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinus officinalis Essential Oil Improves Scopolamine-Induced Neurobehavioral Changes via Restoration of Cholinergic Function and Brain Antioxidant Status in Zebrafish (Danio rerio)

Abstract: Rosmarinus officinalis L. is a traditional herb with various therapeutic applications such as antibacterial, antioxidant, anti-inflammatory, antidepressant, and anticholinesterase activities, and can be used for the prevention or treatment of dementia. In the present study, we tested whether Rosmarinus officinalis L. could counteract scopolamine-induced anxiety, dementia, and brain oxidative stress in the zebrafish model and tried to find the underlying mechanism. Rosmarinus officinalis L. essential oil (REO: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…Accordingly, our behavioral results show that both GGRE and RE improved retention memory as indicated by the T-maze test. Similarly, RE has been shown to improve cognitive function in a zebra sh model of amnesia induced by scopolamine (38). We also found that improvement in retention memory was best at the lowest concentration used (100 mg/L).…”
Section: Discussionsupporting
confidence: 69%
“…Accordingly, our behavioral results show that both GGRE and RE improved retention memory as indicated by the T-maze test. Similarly, RE has been shown to improve cognitive function in a zebra sh model of amnesia induced by scopolamine (38). We also found that improvement in retention memory was best at the lowest concentration used (100 mg/L).…”
Section: Discussionsupporting
confidence: 69%
“…The animals were assigned into ten experimental groups (10 fish per group), each group being housed in 24 L tanks as follow: the control group, the SCOP group, the GAL group (used as a positive control in memory tasks), the IMP group (used as a positive control in anxiety test), two NIC groups (1 and 2 mg/L), two COT groups (1 and 2 mg/L) and two 6HLN groups (1 and 2 mg/L). Before performing a behavioral task, fish (except those from the control group) were individually placed in SCOP solution 100 µM for 30 min to induce the zebrafish model of AD, as previously described [ 36 , 37 , 38 ]. Subsequently, fish were individually subjected to a 3 min acute treatment with 1 and 2 mg/L of NIC, COT, or 6HLN in a 0.5 L pre-treatment beaker ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The doses of Sco, Rho, IMP, and GAL were chosen following a previous report [ 17 ]. Rho (1, 3, and 5 μg/L) was individually delivered to fish through transferring into a 500 mL glass for 1 h, once daily, whereas the Sco (100 μM) treatment was administered once independently by moving into a 500 mL glass 30 min before the behavioral tests [ 18 ]. This study was previously approved by the local board of ethics for animal experimentation (No.…”
Section: Methodsmentioning
confidence: 99%